High bacterial diversity in nearshore and oceanic biofilms and their influence on larval settlement by Hydroides elegans (Polychaeta). (18th June 2019) - Lema, Kimberley A.; Constancias, Florentin; Rice, Scott A.; Hadfield, Michael G.
Summary: Settlement of many benthic marine invertebrates is stimulated by bacterial biofilms, although it is not known if patterns of settlement reflect microbial communities that are specific to discrete habitats. Here, we characterized the taxonomic and functional gene diversity (16S rRNA gene amplicon and metagenomic sequencing analyses), as well as the specific bacterial abundances, in biofilms from diverse nearby and distant locations, both inshore and offshore, and tested them for their ability to induce settlement of the biofouling tubeworm Hydroides elegans, an inhabitant of bays and harbours around the world. We found that compositions of the bacterial biofilms were site specific, with the greatest differences between inshore and offshore sites. Further, biofilms were highly diverse in their taxonomic and functional compositions across inshore sites, while relatively low diversity was found at offshore sites. Hydroides elegans settled on all biofilms tested, with settlement strongly correlated with bacterial abundance. Bacterial density in biofilms was positively correlated with biofilm age. Our results suggest that the localized distribution of H. elegans is not determined by 'selection' to locations by specific bacteria, but it is more likely linked to the prevailing local ecology and oceanographic features that affect the development of dense biofilms and the occurrence of larvae.